The fabric of our souls ebook - Moronova, K. M. (2024)
Two troubled souls find solace in each other at a rehabilitation facility in this spellbinding dark romance sizzling with angst. I’m twenty-six years old, and I want to die. So when I wake up at the hospital with my brother weeping over me, I know my life is about to change. What I didn’t expect was to get a nurse with cruel eyes and a morbid sense of humor that surpasses my own. I’m even more surprised when I arrive at Harlow Sanctum and realize that my brother selected an unorthodox rehabilitation center that rooms people based on their treatment plan. And my roommate is none other than the man with cruel eyes I met the day prior. I crave death—he craves life. Can two people like us cure each other?